(untitled) (CIPEEX, 2025)
Dental Avulsion: Clinical and Epidemiological AspectsThe clinical and epidemiological aspects of permanent tooth avulsion were evaluated in a sample of 280 patients treated at the Emergency Service of the School of Dentistry at the Federal University of Goiás. The following information was collected: the patient’s age at the time of trauma, gender, the tooth involved, the etiological factor of the traumatic injury, the accident location, the time of year, time between the dental trauma and the first treatment, means of transport, extra-oral time, type of splinting, root development stage, treatment performed, and the type of post-trauma complication. The results showed a higher incidence among males (67.86%) in the age group of 11-15 years. The prevalence of traumatic injuries throughout the months of the year was proportional, with a higher number of avulsions observed between March and June (95; 33.93%). The most commonly affected tooth was the maxillary central incisor (65.38%), followed by the maxillary lateral incisor (19.85%). In 189 participants (67.50%), only one tooth was avulsed. A significant proportion (73.80%) of the traumatized teeth had fully formed root apices. The main etiological factors involved in dental trauma were falls (50.36%) and car accidents (25.71%). Dental avulsions mainly occurred in public places (39.64%) and at home (11.79%). Most patients sought treatment after 2 hours (22.22%), with the majority of teeth stored dry (39.45%). A total of 271 teeth (65.62%) were reimplanted, of which 28.78% received semi-rigid splinting and 17.71% rigid splinting. Endodontic treatment with intracanal calcium hydroxide medication was performed in 61.62% of reimplanted teeth. Inflammatory root resorption was observed in 29.79%, 38.24%, and 48.00% of the reimplanted teeth followed up for 1 to 2 years, 2 to 3 years, and over 3 years, respectively. Health promotion policies should be institutionalized to foster the creation of safe environments and disseminate protocols for the proper management of dental avulsion.Keywords: Dental trauma, tooth avulsion, oral epidemiology